Peran Dinas Pertanian Dalam Program Peningkatan Kesejahteraan Petani Di Kabupaten Bima Nusa Tenggara Barat - Anggrianingsih, Wiwing; Razak, Andi Rosdianti; Parawangi, Anwar (Universitas Muhammadiyah Makassar, 2021)
This study aimed to determine the role of the agricultural service in the program to improve the welfare of farmers in the district of West Nusa Tenggara. The type of research used qualitative research. The number of informants in this study was 3 people. Data collection used l observation, interviews with a number of informants such as; the head of the agriculture department, the head of the farmer group and the community. The technique of checking the validity of the data used triangulation, the method triangulation. The data analysis technique used interactive analysis. The results of this study showed that the role of the agricultural service in the program to improve the welfare of farmers in the district of West Nusa Tenggara was good, this was proved by the existence of more advanced developments such as providing technology packages, conducting demonstrations or examples of the use of agricultural technology tools. In this case, farmers used to use traditional tools such as hoe, but now they used tractors. encouraging farmer groups to increase agricultural production, for example they chose superior seeds, subsidized fertilizers, as well as medicines so that the yields obtained increased rapidly without any obstacles.